Orbital modulation in platinum-group-metal (PGM) electrocatalysts: An effective approach to boost catalytic performance - Xuan Liu; Gang Wu; Qing Li (eScience, 2025)
Platinum group metal (PGM) electrocatalysts play an irreplaceable role in many electrochemical reactions for sustainable energy conversion. In the past few decades, the electronic orbital modulation methods have emerged as an important way to produce high-performance electrocatalysts, often by adjusting surface reactivity and enhancing structural stability. In this review, we first systematically elaborate on the basic principles and strategies of orbital modulation for PGM-based catalysts, mainly from the perspective of improving activity and stability, in which we highlight some exploratory theoretical studies over the past few decades. Then we describe a series of representative works to elucidate the specific approaches used to realize precise orbital modulation in PGM catalysts. Finally, we clarify the existing challenges and propose some perspectives for the development of related theories and practical applications.